2013
DOI: 10.1001/jamaoto.2013.5297
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Topical Local Anesthetic and Decongestant for Flexible Nasendoscopy in Children

Abstract: This study revealed no statistically significant difference in the discomfort experienced by children undergoing flexible nasendoscopy after placebo, decongestant, or TLA with decongestant. Decongestant was associated with the least discomfort (on child, caregiver, and observer-rated pain scale scores) and the lowest rating for difficulty of procedure. With these findings, the study suggests that there is no significant benefit of topical decongestant with or without TLA compared with placebo in reducing pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…However, as there was documented evidence that no foreign body was seen on examination under anaesthetic it was placed further down the differential diagnosis list and initially not considered at all. Atypical symptoms such as halitosis, intermittent epistaxis, snoring and obstructive sleep apnoea,3 all which our patient had, should perhaps push clinicians to investigate more promptly in the context of a previous foreign body inhalation. Investigations should also be expedited even in the case of cancellations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, as there was documented evidence that no foreign body was seen on examination under anaesthetic it was placed further down the differential diagnosis list and initially not considered at all. Atypical symptoms such as halitosis, intermittent epistaxis, snoring and obstructive sleep apnoea,3 all which our patient had, should perhaps push clinicians to investigate more promptly in the context of a previous foreign body inhalation. Investigations should also be expedited even in the case of cancellations.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have shown that there is no statistical difference in discomfort for children undergoing flexible nasendoscopy after a placebo, topical anaesthetic or nasal decongestants 3. It should therefore be attempted however, if not tolerable the examination of the postnasal space should take place at the time of general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In young children for whom topical anaesthesia is contraindicated, the administration of oral analgesia, such as acetaminophen, should be performed to decrease suffering. Only one randomised double-blind study13 in children (aged 3–12 years) compared the use of a local anaesthetic (lidocaine hydrochloride 1%) combined with a decongestant (xylometazoline hydrochloride, Nasa Rhinathiol 0.05%) to the use of a decongestant alone (xylometazoline hydrochloride 0.05% nasal spray) or to a placebo (normal saline solution) before performing a flexible nasal endoscopy. This study showed no statistically significant difference between the three solutions as to the level of pain; decongestant nasal spray alone was associated with the lowest score of pain.…”
Section: Methodsmentioning
confidence: 99%
“…Committee consensus: between agree and strongly agree (7.6) multifocal or bilateral malignant thyroid disease (see below). 23,24 Laryngeal US may be considered as an alternative to endoscopy to evaluate vocal fold motion if the examination adequately demonstrates glottic function. 25…”
Section: Historymentioning
confidence: 99%